Management of CBD stones in patients having laparoscopic cholecystectomy in a private setting in Australia. Issue 1 (1st August 2013) - Croagh, Daniel Gerald; Devonshire, David; Poh, Benjamin; Berry, Roger; Bowers, Kaye; Spilias, Dean; Cullinan, Mark; Cashin, Paul
Abstract Introduction Laparoscopic bile duct exploration at the time of laparoscopic cholecystectomy has been promoted as being equally successful as endoscopic bile duct clearance. Further, if successful it offers the possibility of reducing the number of interventions required and therefore reducing overall costs. However, there is little in the literature that describe current treatment patterns in the Australian environment. Methods Medicare data were obtained for the number of patients undergoing laparoscopic cholecystectomy, intraoperative cholangiography, laparoscopic transcystic bile duct exploration, laparoscopic choledochotomy and bile duct exploration, endoscopic retrograde cholangiopancreatography (ERCP), sphincterotomy and endoscopic biliary stent insertion. Results Although there was significant state‐to‐state variation in the prevalence of laparoscopic bile duct exploration (0.6–3.7%), ERCP remained the predominant method of bile duct clearance in the setting of laparoscopic cholecystectomy (5.4%). Transcystic bile duct exploration is far more common than laparoscopic choledochotomy, which is a rare procedure. This suggests that patients with a dilated common bile duct and large or multiple stones are typically undergoing ERCP rather than laparoscopic bile duct clearance. Conclusion Despite the apparent attractiveness of laparoscopic bile duct exploration at the time of cholecystectomy, ERCP remains the most common method of dealing with choledocholithiasis in the setting of an intact gallbladder in Australia.